Упростите пожалуйста выражение Задание во вложении

Упростите пожалуйста выражение Задание во вложении
Гость
Ответ(ы) на вопрос:
Гость
[latex](2a+ \frac{2ab}{2a+b}-b ):(1+ \frac{2ab}{4a^2-b^2} )-a+2b=[/latex] [latex]=\frac{2a(2a+b)+2ab-b(2a+b)}{2a+b}:\frac{4a^2-b^2+2ab}{4a^2-b^2}-a+2b=[/latex] [latex]=\frac{4a^2+2ab+2ab-2ab-b^2}{2a+b}*\frac{4a^2-b^2}{4a^2-b^2+2ab}-a+2b=[/latex] [latex]=\frac{4a^2-b^2+2ab}{2a+b}*\frac{(2a)^2-(b)^2}{4a^2-b^2+2ab}-a+2b=[/latex] [latex]=\frac{(4a^2-b^2+2ab)(2a-b)(2a+b)}{(2a+b)(4a^2-b^2+2ab)}-a+2b =2a-b-a+2b=a+b[/latex]
Гость
1)(2a-b)+2ab/(2a+b)=(4a²-b²+2ab)/(2a+b) 2)1+2ab/(4a²-b²)=(4a²-b²+2ab)/(4a²-b²) 2)(4a²-b²+2ab)/(2a+b)*(2a+b)(2a-b)/(4a²-b²+2ab)=2a-b 4)2a-b-a+2b=a+b
Не нашли ответ?
Ответить на вопрос
Похожие вопросы